The use of cassava leaves as food in Africa - Achidi, A.; Ajayi, O.; Maziya-Dixon, B.B.; Bokanga, M. (Informa UK Limited, 2005)
The rate of cassava leaf consumption in Africa was assessed by a combination of informal interviews, the use of questionnaires and information from the literature. Countries were rated to have high, average, low, or no consumption of cassava leaves. The mode of cassava leaf preparation was studied with six housewives who are nationals of Congo (3), Sierra Leone (1), Madagascar (1), and Nigeria (1). In each case, the procedure was observed from leaf-picking in the field to serving the cooked dish. The first matured leaf up to leaf position 9 or 10 were selected for consumption. The tender petioles and stem were also taken. There were country variations in the preference for particular varieties based on petiole color and mild mosaic infection. Prior to cooking, cassava leaves are usually pounded or ground but pounding is the most popular method. The recipes from Sierra Leone and Nigeria took 40–60 minutes while the standard Congolese recipe took 90 minutes. However, there is a Congolese recipe using sodium bicarbonate that cooks in only 20 minutes. From the comments made by 50 interview respondents from different African countries, it appears that there is a wide variety of cassava leaf based recipes suggesting that cassava leaves are a major food in Africa.